Synthesis of High-Energy Polymer – Glycidyl Azide Polymer (GAP) - Anna KASZTANKIEWICZ (Synteza wysokoenergetycznego polimeru – poliazydku glicydylu (GAP), 2018)
Glycidyl Azide Polymer (glycidyl polyazide) (GAP) is one of the best known energetic binders, applicable as a component increasing a calorific value of rocket propellants. In this article, a synthesis of GAP is described allowing to obtain a polymer of different molecular masses. The change of a molecular mass can influence on properties of the obtained compounds. The synthesis was carried out according to an active monomer mechanism. The obtained products were characterized using such methods as FTIR, GPC, MALDI-ToF, TG, and NMR.
Keywords: Technologia materiałów wybuchowych